Dye Tracking Following Posterior Semicircular Canal or Round Window Membrane Injections Suggests a Role for the Cochlea Aqueduct in Modulating Distribution - Talaei, Sara; Schnee, Michael E.; Aaron, Ksenia A.; Ricci, Anthony J. (Frontiers in Cellular Neuroscience, 2019)
The inner ear houses the sensory epithelium responsible for vestibular and auditory function. The sensory epithelia are driven by pressure and vibration of the fluid filled structures in which they are embedded so that understanding the homeostatic mechanisms regulating fluid dynamics within these structures is critical to understanding function at the systems level. Additionally, there is a growing need for drug delivery to the inner ear for preventive and restorative treatments to the pathologies associated with hearing and balance dysfunction. We compare drug delivery to neonatal and adult inner ear by injection into the posterior semicircular canal (PSCC) or through the round window membrane (RWM). PSCC injections produced higher levels of dye delivery within the cochlea than did RWM injections. Neonatal PSCC injections produced a gradient in dye distribution; however adult distributions were relatively uniform. RWM injections resulted in an early base to apex gradient that became more uniform over time, post injection. RWM injections lead to higher levels of dye distributions in the brain, likely demonstrating that injections can traverse the cochlea aqueduct. We hypothesize the relative position of the cochlear aqueduct between injection site and cochlea is instrumental in dictating dye distribution within the cochlea. Dye distribution is further compounded by the ability of some chemicals to cross inner ear membranes accessing the blood supply as demonstrated by the rapid distribution of gentamicin-conjugated Texas red (GTTR) throughout the body. These data allow for a direct evaluation of injection mode and age to compare strengths and weaknesses of the two approaches. PSCC injection delivers a more uniform and higher level of dye to the cochlea compared to RWM injection.